2005
DOI: 10.1002/elan.200403086
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Enzymeless/Mediatorless Glucose Sensor Using Ruthenium Oxide‐Prussian Blue Combinative Analogue

Abstract: Presented in this work is the first step towards an enzymeless/mediatorless glucose sensor. We first observed remarkable electrocatalytic oxidation of glucose using combinative ruthenium oxide (RuOx)-Prussian blue (PB) analogues (designated as mvRuOx-RuCN, mv: mixed valent) at ca. 1.1 V (vs. Ag/AgCl) in acidic media (pH 2 Na 2 SO 4 / H 2 SO 4 ). Individual RuOx and PB analogs failed to give any such catalytic response. A high ruthenium oxidation state (i.e., oxy/hydroxy-Ru VII , E8 % 1.4 V vs. RHE), normally o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 67 publications
0
25
1
Order By: Relevance
“…One linear calibration range from 0.05 to 20 mM (R ¼ 0:9974) with a sensitivity of 0.018 mA/mM was obtained. This linear range was also wider than those of 0.07-15 mM [8] and 0.3-20 mM [27] with flow injection analysis. The response time was also very fast.…”
Section: Flow Injection Analysiscontrasting
confidence: 46%
“…One linear calibration range from 0.05 to 20 mM (R ¼ 0:9974) with a sensitivity of 0.018 mA/mM was obtained. This linear range was also wider than those of 0.07-15 mM [8] and 0.3-20 mM [27] with flow injection analysis. The response time was also very fast.…”
Section: Flow Injection Analysiscontrasting
confidence: 46%
“…XPS and ATIR/FTIR characterization provided useful supporting information regarding the surface functionalities and topology of the activated-and CA adsorbed-carbon surfaces. Since the activation procedure is simple and selective to immobilize the CA, it is highly useful to construct a variety of electrochemical and biochemical sensors , especially using fixed potential flow-injection analysis coupled electrochemical detector, where the initial instability problems noticed with potential-cycling studies could be overcome [22]. Further work is in progress.…”
Section: Resultsmentioning
confidence: 99%
“…The electro-oxidation of glucose and certain other monosaccharides were studied on various metals (Pt, Au, Pd, Cu and Ni) and their alloys (Pt-Pb, Pt-Ru, Pt-Au and Cu-Ni), and also on modified surfaces such as ruthenium dioxide, cobalt oxide (Co 3 O 4 ) and nickel oxide. [16][17][18][19] In a previous report, it was shown that the size of Ni (OH) 2 nanoparticles (NPs) played a vital role on their electrocatalytic activity toward glucose oxidation. However, the electrocatalytic activity not only depends on size, morphology, surface texture, and crystalline structure of nanomaterials, but also on the nature of the support.…”
Section: Introductionmentioning
confidence: 99%